2019
DOI: 10.1111/jcmm.14565
|View full text |Cite
|
Sign up to set email alerts
|

Co‐mutational assessment of circulating tumour DNA (ctDNA) during osimertinib treatment for T790M mutant lung cancer

Abstract: Osimertinib is designed to target the secondary resistant EGFR T790M mutant and has shown outstanding clinical efficacy. However, the prognostic prediction of osimertinib patients is a big problem in clinical practice. The resistance mechanism of osimertinib is also not fully understood. NGS and a 1021 gene capture panel were used to analyse the somatic mutation profile of thirty‐six lung adenocarcinoma patients' serial ctDNA samples. Progression‐free survival of subgroup patients is analysed. Patients harbour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…K754I conferred resistance against osimertinib in both the presence and absence of T790M; it was classified as having an intermediate effect in the afatinib arm. This result is compatible with a case report about a patient bearing T790M, in which osimertinib treatment led to loss of the T790M-encoding SNV but enriched that encoding K754I 57 .…”
Section: Maintextsupporting
confidence: 91%
“…K754I conferred resistance against osimertinib in both the presence and absence of T790M; it was classified as having an intermediate effect in the afatinib arm. This result is compatible with a case report about a patient bearing T790M, in which osimertinib treatment led to loss of the T790M-encoding SNV but enriched that encoding K754I 57 .…”
Section: Maintextsupporting
confidence: 91%
“…In addition, the mechanism of the difference in T790M mutation status when patients acquired resistance to Osimertinib remains unclear. The most likely explanation may be the genomic heterogeneity inherent in the tumor before the treatment with Osimertinib [26,27]. As previously reported, concomitant genomic alterations are widespread in lung cancer [28], and the T790M-positive and wild-type cell clones may co-exist in tumors at baseline levels or after acquired resistance to pre-EGFR TKI [29].…”
Section: Discussionmentioning
confidence: 91%
“…The tumor heterogeneity was attributed to both genetic and non‐genetic mechanisms acting at various intervals for targeted drugs, including EGFR‐TKIs in NSCLC patients with EGFR mutations 26,27 . TMB, CIS, and MATH scores help to evaluate intratumor genetic heterogeneity, which is closely related to drug resistance and poor outcomes in patients with lung cancer harboring EGFR mutations 28–33 . In this study, gefitinib‐resistant cells showed diverse CIS, TMB, and MATH scores compared with dacomitinib‐induced resistant cells, suggesting that the wide range of inhibitory activity of dacomitinib might prevent gene alterations and yield a low proportion of sub‐clones with EGFR ‐T790M mutation 23 .…”
Section: Discussionmentioning
confidence: 74%